Behind the doors of home hospice patients: A secondary qualitative analysis of hospice nurse communication with patients and families. Issue 5 (October 2019) - Oliver, Debra Parker; Tappana, Jessica; Washington, Karla T.; Rolbiecki, Abigail; Craig, Kevin; Demiris, George; Schafer, Collyn; Winjobi, Mumeenat; Clayton, Margaret F.; Reblin, Maija; Ellington, Lee
Abstract: Objective: Hospice nurses frequently encounter patients and families under tremendous emotional distress, yet the communication techniques they use in emotionally charged situations have rarely been investigated. In this study, researchers sought to examine hospice nurses' use of validation communication techniques, which have been shown in prior research to be effective in supporting individuals experiencing emotional distress. Method: Researchers performed a directed content analysis of audiorecordings of 65 hospice nurses' home visits by identifying instances when nurses used validation communication techniques and rating the level of complexity of those techniques. Result: All nurses used validation communication techniques at least once during their home visits. Use of lower level (i.e., more basic) techniques was more common than use of higher level (i.e., more complex) techniques. Significance of Results: Although hospice nurses appear to use basic validation techniques naturally, benefit may be found in the use of higher level techniques, which have been shown to result in improved clinical outcomes in other settings.